The obstacles of differentiated education strategy in teaching Arabic language from the viewpoint of subject teachers in Aqaba Governorate in Jordan - Al-bordeini, Mohammad Hijazi Khalil (Journal of Educational and Psychological Sciences, 2020)
The present study aimed to reveal the degree of the obstacles of differentiated education strategy in teaching Arabic language from the viewpoint of subject teachers in Aqaba Governorate in Jordan. The researcher used the descriptive analytical method, and the tool was represented in a questionnaire, which was applied to a sample of (150) teachers, who represent (100%) of the study population, including (64) teachers, and (86) teachers. The results of the study showed that the total score of obstacles to using the differentiated education strategy in teaching Arabic from the viewpoint of subject teachers in Aqaba Governorate obtained an average of 3.59 out of 5), with a (large) estimate. and at the level of fields; the field of obstacles related to management got the highest average (3.77) And, in large measure, followed by obstacles related to the learner with an average of (3.71), and in large degree, then the obstacles related to the curriculum with Mediated (3.47), with an intermediate degree, then with teacher-related obstacles (3.43), with an intermediate degree. The results of the analysis of variance showed that there are significant differences in the degree of obstacles to using the differentiated education strategy in teaching Arabic language due to the variable of experience and in favor of their experience (11 years or more), while there are no significant differences for the gender variable. According to the results, a number of recommendations and proposals were presented to overcome the obstacles and activate the teaching of the Arabic language in Aqaba Governorate, in the whole of the Kingdom of Jordan and the Arab countries.